Penanaman Nilai-nilai Pendidikan Agama Kristen pada Peserta Didik dengan Pendekatan Evolusi Sosial Herbert Spencer - Hutapea, Rinto Hasiholan (Harati: Jurnal Pendidikan Kristen, 2024)
This study aims to analyze the cultivation of students' Christian Religious Education values with Herbert Spencer's social evolution approach. The literature review method is the approach used in this research. The results show that the process of social evolution starts from individuals who combine themselves into a family, the family joins into a community, the community becomes a society, and the society becomes a state, and so on is a development that emphasizes the process. The planting of Christian Religious Education values in students is the same, that every stage of behavioral and spiritual development of students requires a process. The process referred to here is an effort made by Christian Religious Education teachers to guide and educate students to the realization of Christian Religious Education values in the real lives of students.